Evaluation of Bike Racing Development for ISSI Athletes in Banyuasin Regency - Norman, Norman; Lian, Bukman; Imansyah, Farizal (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this study was to determine the coaching of bicycle racing for ISSI athletes in Banyuasin Regency. This research was conducted at ISSI Banyuasin. The objects in this study were KONI, trainers, athletes, administrators of ISSI Banyuasin. The research method used in this study is a qualitative descriptive method. The data used in this study is data in qualitative form. Data collection techniques in this study include observation, documentation, and interviews. Data analysis techniques used Miles and Huberman which included data reduction, data display, and conclusion drawing. Based on the discussion that has been stated above, it can be interpreted that the coaching of bicycle racing for ISSI athletes in Banyuasin Regency has been running according to technical support but there are still weaknesses. The bicycle racing development is carried out by eliminating athletes, filling in trainers, training exercises, adequacy of athletes’ nutritional intake, lodging, evaluation, management, completeness of training facilities and infrastructure, and financing has not gone well. In addition, coaching for cycling athletes, namely Koni administrators and ISSI administrators in Banyuasin Regency also have their own roles to advance the sport of cycling and are responsible for coaching bicycle racing athletes and bicycle racing trainers.